The financial cost of export credit guarantee programs - Henry, Donald Putnam, 1957-; National Defense Research Institute (U.S.). International Economic Policy Program; Rand Corporation; United States. Office of the Under Secretary of Defense for Policy (Santa Monica, CA : RAND, 1987)
This report examines the financial performance of export credit guarantee programs. This performance is closely related to the subsidization of official export credits. The Export-Import Bank of the United States (Eximbank), contrary to its financial reports, is shown to be deeply in the red. Comparisons are then made between Eximbank's performance and the performance of similar agencies in other Organization for Economic Cooperation and Development (OECD) nations.
"June 1987."
"National Defense Research Institute"--Cover.
Includes bibliographical references (p. 37).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Export credit -- United States; Insurance, Export credit -- United States